Cluster tools for organizing tourism - Navruz-zoda Zebiniso Bakhtiyorovna (THE INNOVATION ECONOMY, 2026)
The article examines in detail the essence of regional concentration, vertical integration, horizontal cooperation, added value chain, competitive benchmarking and destination marketing as cluster tools of tourism organization, and ways of their practical application at the regional level are determined.